The Antisenescence Effect of Trans-Cinnamaldehyde on Adipose-Derived Stem Cells. Issue 3 (March 2015) - Rajamani, Karthyayani; Lin, Yi-Chun; Wen, Tung-Chou; Hsieh, Jeanne; Subeq, Yi-Maun; Liu, Jen-Wei; Lin, Po-Cheng; Harn, Horng-Jyh; Lin, Shinn-Zong; Chiou, Tzyy-Wen
As assuring cell quality is an essential parameter for the success of stem cell therapy, the impact of various senescence-inducing stress signals, and strategies to circumvent them, has been an important area of focus in stem cell research. The aim of this study was to demonstrate the capacity of trans -cinnamaldehyde (TC) in reversing stress-induced senescence and maintaining the quality of stem cells in a chemically (H2 O2 )-induced cell senescence model. Because of the availability and the promising application potential in regenerative medicine, adipose-derived stem cells (ADSCs) were chosen for the study. We found that H2 O2 treatment resulted in the expression of senescence characteristics in the ADSCs, including decreased proliferation rate, increased senescence-associated β-galactosidase (SA-β-gal) activity, decreased silent mating type information regulation 2 homolog ( SIRT1 ) expression, and decreased telomerase activity. However, TC treatment was sufficient to rescue or reduce the effects of H2 O2 induction, ultimately leading to an increased proliferation rate, a decrease in the percentage of SA-β-gal-positive cells, upregulation of SIRT1 expression, and increased telomerase activity of the senescent ADSCs at the cellular level. Moreover, a chemically induced liver fibrosis animal model was used to evaluate the functionality of these rescued cells in vivo. Liver dysfunction was established by injecting 200 mg/kg thioacetamide (TAA) intraperitoneally into Wistar rats every third day for 60 days. The experimental rats were separated into groups: normal group (rats without TAA induction), sham group (without ADSC transplantation), positive control group (transplanted with normal ADSCs), H2 O2 group (transplanted with H2 O2 -induced senescent ADSCs), and H2 O2 + TC group (transplanted with ADSCs pretreated with H2 O2 and then further treated with TC). In the transplantation group, 1 × 10 6 human ADSCs were introduced into each rat via direct liver injection. Based on the biochemical analysis and immunohistochemical staining results, it was determined that the therapeutic effects on liver fibrosis by the induced senescent ADSCs (H2 O2 group) were not as significant as those exerted by the normal ADSCs (the positive control group). However, the H2 O2 + TC group showed significant reversal of liver damage when compared to the H2 O2 group 1 week posttransplantation. These data confirmed that the TC treatment had the potential to reduce the effects of H2 O2 -induced senescence and to restore in vivo functionality of the induced senescent ADSCs. It is therefore suggested that TC has potential applications in maintaining the quality of stem cells and could aid in treating senescence-related disorders.